Upaya Meningkatkan Kemandirian Belajar Siswa Berbantu Teknik Shaping - Chusnul Khotimah; Esa Nur Wahyuni; Devi Permatasari; Leny Latifah (JKI (Jurnal Konseling Indonesia), 2021)
A phenomenon that is often encountered today is that many students have low learning independence. Students who have low learning independence often depend on their friends during the learning process, so they rely more on other friends. This study aims to determine how effective the shaping technique can help increase the learning independence of elementary school students. This study uses an experimental design with a single-subject design. This single case experimental study uses the A-B-A design. Data collection was carried out using observation and interviews. The subjects of this study were 4 5th grade students of SD Dadapan 01, Wajak District, Malang Regency who had a low level of learning independence. Quantitative data was analyzed visually, while qualitative data were presented descriptively. The length of the conditions during phase (A1) was 4 sessions, the intervention phase (B) was 6 sessions, and phase (A2) was 4 sessions. Based on the data-trace line, it can be seen that the phase (A1) of the trace data is low. The intervention phase (B) has an increasing data footprint and in-phase (A2) the data trail is increasing and stable. Data for baseline phase 1 (A1) is low with susceptibility 4-6, intervention phase (B) increases stably with susceptibility to 21-35, and baseline phase 2 (A2) increases stably with susceptibility to 17-21. The results of group analysis can be concluded that treatment assistance with shaping techniques can increase learning independence.